THE IMPLEMENTATION OF DISCOVERY LEARNING METHOD IN EXTENSIVE READING PROGRAMS TO BOOST READING MOTIVATION AND COMPREHENSION - Sufiana Sufiana; Riski Zulkarnain; Nove Kurniati Sari; Oasis D’Arafah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The persistent challenge of low reading motivation and comprehension among English as a Foreign Language (EFL) learners necessitates innovative pedagogical interventions. This study investigates the implementation of Discovery Learning Method within extensive reading programs as a means to enhance both reading motivation and comprehension among Indonesian university students. Employing a Classroom Action Research (CAR) design conducted over two iterative cycles, the research involved 31 undergraduate students enrolled in an English Class. Data were collected through pre- and post-tests, reading motivation questionnaires, classroom observations, and reflective journals. The intervention integrated Discovery Learning principles—stimulation, problem statement, data collection, data processing, verification, and generalization—into extensive reading sessions where students autonomously selected reading materials and constructed meaning through guided discovery. Quantitative findings revealed substantial improvements across both cycles: mean reading comprehension scores increased from 53.87 (Cycle I) to 73.55 (Cycle II), while reading motivation scores rose from 65.3 to 81.2. Qualitative data indicated enhanced student engagement, increased autonomous learning behaviors, and improved critical thinking skills. The study demonstrates that Discovery Learning Method, when systematically integrated into extensive reading programs, creates a synergistic effect that simultaneously addresses motivational and cognitive dimensions of reading. These findings contribute to the theoretical understanding of constructivist approaches in L2 reading pedagogy and offer practical implications for curriculum designers and English language educators seeking evidence-based strategies to foster meaningful reading engagement in EFL contexts. Keywords: Discovery Learning, Extensive Reading, Reading Motivation, Reading Comprehension, Classroom Action Research, EFL Pedagogy, Constructivist Learning Abstrak: Tantangan yang berkelanjutan berupa rendahnya motivasi dan pemahaman membaca pada pembelajar Bahasa Inggris sebagai Bahasa Asing (EFL) menuntut adanya intervensi pedagogis yang inovatif. Penelitian ini menginvestigasi implementasi Metode Discovery Learning dalam program membaca ekstensif sebagai upaya untuk meningkatkan motivasi dan pemahaman membaca mahasiswa perguruan tinggi di Indonesia. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus iteratif dan melibatkan 31 mahasiswa pada kelas bahasa Inggris. Data dikumpulkan melalui pre-test dan post-test, angket motivasi membaca, observasi kelas, serta jurnal reflektif. Intervensi penelitian mengintegrasikan prinsip-prinsip Discovery Learning—stimulasi, perumusan masalah, pengumpulan data, pengolahan data, verifikasi, dan generalisasi—ke dalam sesi membaca ekstensif, di mana mahasiswa secara mandiri memilih bahan bacaan dan mengonstruksi pemahaman melalui proses penemuan yang terarah. Temuan kuantitatif menunjukkan peningkatan yang signifikan pada kedua siklus: rata-rata skor pemahaman membaca meningkat dari 53,87 (Siklus I) menjadi 73,55 (Siklus II), sedangkan skor motivasi membaca meningkat dari 65,3 menjadi 81,2. Data kualitatif mengindikasikan adanya peningkatan keterlibatan mahasiswa, berkembangnya perilaku belajar mandiri, serta peningkatan keterampilan berpikir kritis. Penelitian ini menunjukkan bahwa Metode Discovery Learning, ketika diintegrasikan secara sistematis dalam program membaca ekstensif, menghasilkan efek sinergis yang secara simultan mengakomodasi dimensi motivasional dan kognitif dalam aktivitas membaca. Temuan ini berkontribusi terhadap penguatan pemahaman teoretis mengenai pendekatan konstruktivis dalam pedagogi membaca bahasa kedua serta memberikan implikasi praktis bagi perancang kurikulum dan pendidik bahasa Inggris yang mencari strategi berbasis bukti untuk menumbuhkan keterlibatan membaca yang bermakna dalam konteks EFL. Kata Kunci: Discovery Learning, Membaca Ekstensif, Motivasi Membaca, Pemahaman Membaca, Penelitian Tindakan Kelas, Pedagogi EFL, Pembelajaran Konstruktivis